Pengaruh Endorser Credibility terhadap Brand Equity ‘Shopee For Men’ dengan Self-Brand Connection sebagai Mediator - Ade Multi Davista Sari; Citra Kusuma Dewi (Jurnal Sekretaris dan Administrasi Bisnis, 2019)
Shopee is one of the markets that provide online trading platforms in Indonesia. Shopee is known by consumers as a brand associated with brands only for women. Though Shopee is a neutral market and is aimed at all circles. Brand equity. This will have an impact on consumer preferences including male consumers of the Shopee brand. Shopee has a strategy by launching the "Shopee for Men" program and using Bambang Pamungkas and Vincent Rompies as supporters to change consumer perceptions that Shopee is a market for all people and forms Shopee brand equity. The factor that can shape the equity band is the credibility of endorsers and their own brand connections. Therefore the purpose of this study was to determine the effect of endorser credibility on brand equity with self-brand connection as a mediator. This study uses a quantitative method with a type of descriptive causal research. The sampling technique in this study was purposive sampling which is a part of non probability. Respondents from this study were 100 consumers with male sex living on the island of Java. This study uses SEM-PLS data analysis techniques. The results of this study are endorser credibility, brand equity and self-brand connections in Shopee For Men in the high category. There is a positive influence between credibility of endorsers and brand equity and self-brand connections have an indirect influence or as a mediator between credibility of endorsers and brand equity.